Replication Data for: A Computational Protocol for VCD spectra of Cyclic Peptides ... - Eikås, Karolina Di Remigio; Ruud, Kenneth; Beerepoot, Maarten T. P. (DataverseNO, 2022)
This dataset contains output files for a conformational search (CREST 2.8), optimized geometries, frequencies and Vibrational Circular Dichroism (VCD) properties (Gaussian 16 Rev. B.01) for the seven molecules cyclo(Ala-bAla-Ala-bAla), Cyclo(Ala-bAla-Pro-bAla), Cyclo(Pro-bAla-Pro-bAla), Cyclo(Boc-Cys-Pro-Gly-Cys-OMe), Cyclo(Boc-Cys-Pro-L-Leu-Cys-OMe), Cyclo(Boc-Cys-Pro-R-Leu-Cys-OMe) and Cyclo(Phe-D-Pro-Gly-Arg-Gly-Asp). The conformational search is done with CREST while the rest is done with GAUSSIAN 16. For more information about the computational protocols used to generate the data, please see the journal article. For Cyclo(Boc-Cys-Pro-R-Leu-Cys-OMe) the geometry of the transition state between conformers is identified with a NEB-TS calculations using the ORCA 5.0 software, while the frequencies and energies are calculated with Gaussian 16 Rev. B.01. Some of the zip files are large and we recommend to download with URL, see "Download via URL" here: ...